The Theoretical Analysis of the Curve of Photoconductivity vs. Irradiation Time (2): The Effect of Electric-conductive Lattice Defects - SUZUKI, Shin (The Journal of The Society of Scientific Photography of Japan, 1963)
The effect of concentration of lattice defects in ionic crystal upon photoconductivity was investigated by using theoretical equation on photoconductivity vs. irradiation time. The results showed that the decrease of photoconductive positive effect was decreased with the increase of the concentration. This tendency agreed well with the experimental results.